(untitled) (Global Journal of Science Frontier Research, 2023)
A soil hydraulic capacitance is a new physical property related to the interactions between the agro eco-system components soil, water, plant and atmosphere. It gives new quantitative details about the processes control the plant water uptake, ascending of sap and soil response toward the root water uptake under a certain soil moisture regime and climatic changes. The soil hydraulic capacitance, a tank like a plant water reservoir, is being controlled by signals, valves like switches. Three types of signaling devices, Geo, Bio, and weather controlled were discussed. The soil hydraulic capacitance property was first discovered by the author when modeling the wheat root water uptake under saline and drought conditions. Under the latter extreme conditions, treating plants with silica products was the managerial practice used for enhanced plant growth and water uptake. A split-split plot experimental design with four replicates was used to conduct the research in Oraby Village, Maryout area, Alexandria, Egypt in the last year of the most water-scarce decade.